2020
DOI: 10.3102/0013189x20912758
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Are People Too: Examining the Racial Bias of Teachers Compared to Other American Adults

Abstract: Schools are heralded by some as unique sites for promoting racial equity. Central to this characterization is the presumption that teachers embrace racial equity and teaching about this topic. In contrast, others have documented the ongoing role of teachers in perpetuating racial inequality in schools. In this article, we employ data from two national data sets to investigate teachers’ explicit and implicit racial bias, comparing them to adults with similar characteristics. We find that both teachers and nonte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 65 publications
8
119
0
Order By: Relevance
“…(Smith, 2018, para. 9) The authors of recent U.S. research (Starck et al, 2020) say their findings resonate with the studies of social reproduction by sociologists Bowles and Gintis (1976) and Bourdieu and Passeron (1990) in recognising that 'schools are best understood as microcosms of society rather than as antidotes to inequality' in that the degree of racism reflected in the teaching profession mirrors that of the wider society (Starck et al, 2020, p. 9).…”
Section: Discussion -A Herd Of 'Elephants' and Some Implicationsmentioning
confidence: 94%
“…(Smith, 2018, para. 9) The authors of recent U.S. research (Starck et al, 2020) say their findings resonate with the studies of social reproduction by sociologists Bowles and Gintis (1976) and Bourdieu and Passeron (1990) in recognising that 'schools are best understood as microcosms of society rather than as antidotes to inequality' in that the degree of racism reflected in the teaching profession mirrors that of the wider society (Starck et al, 2020, p. 9).…”
Section: Discussion -A Herd Of 'Elephants' and Some Implicationsmentioning
confidence: 94%
“…The final group consisted of six administrators as presented in Table 2 , where two administrators represented demographic subgroups of Color with one identifying as Black and the other as Latina. Based on the findings of Starck and colleagues (2020) that teacher implicit bias is reflective of racial biases in the general population and the associated patterns of disciplinary disproportionality based on bias levels ( Chin et al., 2020 ), the administrators in this sample are expected to mirror that of most districts where discipline discrepancies exist.…”
Section: Methodsmentioning
confidence: 99%
“…Implicit biases tend to act on students’ academics via teacher expectations, teacher traits, curricular materials, and access; and on student discipline via teacher determination of misbehavior, teacher reactions to behavior, and administrator reactions to discipline referrals. According to Starck and colleagues (2020) , teacher patterns of implicit bias reflect that of the general population. As such, the pattern of teacher implicit bias logically extends to that of educational leaders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Educators’ implicit racial biases are of particular interest due to their potential consequences for students (Quinn, 2017; Starck et al, 2020; Warikoo et al, 2016). Findings from noneducational settings (Dovidio et al, 2002) lead one to expect that teachers’ negative implicit attitudes toward different racial groups will influence their demeanor and warmth when interacting with students and families from those groups.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from outside the United States have shown that teachers’ levels of implicit bias (as measured by the IAT) toward racial/ethnic minorities is associated with test score inequalities within teachers’ classrooms (Peterson et al, 2016; van den Bergh et al, 2010), and similar results have been found for gender bias (Carlana, 2019). In the United States, teachers and nonteachers exhibit similar levels of implicit bias overall (Starck et al, 2020), and teachers with higher levels of racial bias on the IAT were less likely to report that they promoted mutual respect among students in their classrooms (Kumar et al, 2015). In an experimental study, Black—but not White—college students learned less when taught by a White college student with higher levels of implicit racial bias (as measured by a subliminal priming task), and this effect seemed to be mediated by instructor anxiety and instructional quality (Jacoby-Senghor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%